1997
DOI: 10.1055/s-2007-979027
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D Receptor Expression in Chicken Muscle Tissue and Cultured Myoblasts

Abstract: Muscle has long been recognized as a target tissue for 1,25-dihydroxy-vitamin D3 (1,25[OH]2D3). Evidence of the presence of VDR is provided here, thus supporting the existence of a receptor-mediated mechanism of action of 1,25(OH)2D3. Vitamin D receptor (VDR) expression is evidenced by detection of VDR-mRNA, through reverse transcription and polymerase chain reaction (RT/PCR), in chicken muscle and muscle cells (myoblasts) as well as in a variety of tissues such as intestine, kidney, heart and brain. VDR prese… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
20
0
1

Year Published

1998
1998
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(23 citation statements)
references
References 12 publications
0
20
0
1
Order By: Relevance
“…The activation process of the glucocorticoid receptor (GR), androgen receptor, and progesterone receptor also includes a translocation of these receptors from the cytoplasm to the nucleus. For many years, however, VDR has been considered to reside exclusively in the nucleus even without hormone (8,9). More recently, significant amounts of unliganded VDR was found in the cytoplasm with immunocytology (10,11) and with fluorescent labeled hormone in living cells (12).…”
Section: The Vitamin D Receptor (Vdr)mentioning
confidence: 99%
“…The activation process of the glucocorticoid receptor (GR), androgen receptor, and progesterone receptor also includes a translocation of these receptors from the cytoplasm to the nucleus. For many years, however, VDR has been considered to reside exclusively in the nucleus even without hormone (8,9). More recently, significant amounts of unliganded VDR was found in the cytoplasm with immunocytology (10,11) and with fluorescent labeled hormone in living cells (12).…”
Section: The Vitamin D Receptor (Vdr)mentioning
confidence: 99%
“…Early clinical descriptions of a reversible myopathy associated with vitamin D deficiency and/or chronic renal failure recognized a potential association between vitamin D and muscle (Boland, 1986). The identification of the vitamin D receptor (VDR) on muscle cells (Zanello et al, 1997;Bischoff et al, 2001) provided further support for a direct effect of vitamin D on muscle tissue. Recent investigations in cell culture and animals have advanced our understanding of some of the molecular mechanisms through which vitamin D targets skeletal muscle; however, much remains to be characterized.…”
Section: Introductionmentioning
confidence: 99%
“…These experiments also revealed that the apparent nuclear/cytosol distribution depends upon the ionic strength of the extraction buffer used in the subcellular fractionation procedure [Walters et al, 1980]. Nevertheless, immunocytochemical localization studies confirm that, in situ, VDR is primarily a nuclear protein even in the ligand unoccupied state [Berger et al, 1988;Clemens et al, 1988;Milde et al, 1989;Zanello et al, 1997] .…”
mentioning
confidence: 99%